Optimizing Financial Literacy and Financial Technology in Improving the Performance of Sasirangan MSMEs in Banjarmasin: The Role of Financial Management Behavior - Bustani Bustani; Mailiana Mailiana; Nasrullah Nasrullah; Riska Sartika (Ilomata International Journal of Social Science, 2026)
This study examines the impact of financial literacy and the adoption of financial technology on financial management practices and the performance of Sasirangan MSMEs in Banjarmasin, highlighting the mediating role of financial management behavior. Although vital to the national economy, Sasirangan MSMEs face challenges in financial management and digital integration. The primary research question investigates how financial literacy and the utilization of financial technology influence financial management practices and overall MSME performance. By addressing a gap in the existing literature, this study analyzes the mediating role of financial management behavior between financial literacy, financial technology, and MSME performance, specifically within Sasirangan MSMEs. Utilizing a quantitative approach with PLS-SEM, data were gathered from 66 Sasirangan MSME owners in Banjarmasin. The findings demonstrate that financial literacy significantly impacts financial management behavior, which mediates the relationship between financial literacy and MSME performance. Furthermore, adopting financial technology enhances financial management behavior and MSME performance, with financial management behavior acting as a mediator. The study concludes that improving financial management behavior through financial literacy and technology adoption is vital for enhancing the performance of Sasirangan MSMEs. These results suggest that fostering improved financial management behavior is essential for promoting sustainable growth in local MSMEs. Future studies should examine external factors, such as government policies, that affect MSME financial management practices.